KOMPETENSI PERILAKU KERJA ASN PADA PEMERINTAH DAERAH ACEH - Idarafni (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2021)
State Civil Apparatus (ASN) has often been equipped with knowledge, skills and work behavior through education and training carried out by the Aceh Human Resources Development Agency (BPSDM). To face the changing times, an innovative ASN work behavior is needed to create good and quality governance. However, to this date, ASN has not yet shown any innovative work behavior reflected in their jobs. The obtained data were analyzed by using the analysis mechanism in qualitative research. The results revealed that, first, the competency of ASN work behavior in the commitment aspect includes facilitating services, making sacrifices, working with targets, and having self-discipline. Second, the competency in the earnestness aspect refers to having independent learning. Third, the competency in the loyalty aspect includes creating teamwork. And fourth, however, in terms of the professional aspect, the competency of ASN work professionalism is still low.